ANALISIS IMPLEMENTASI HIRI DAN OTTAPPA TERHADAP PENCEGAHAN PERILAKU BULLYING PADA SISWA SMB AMAN SEJAHTERA SEMPARUK - Mursidi; Mettadewi Wong; Mujiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is motivated by the increasing prevalence of bullying, both directly and through social media, which occurs not only in formal schools but also in Buddhist Sunday Schools (Sekolah Minggu Buddha/SMB). Such phenomena cause intimidation, discrimination, and trauma that disrupt the learning process and contradict Buddhist values emphasizing loving-kindness and self-restraint. The purpose of this study is to analyze the implementation of the values of Hiri (a sense of shame in committing wrongdoing) and Ottappa (fear of the consequences of misconduct) as efforts to prevent bullying at SMB Aman Sejahtera Semparuk. The research employed a descriptive qualitative method with participants consisting of three teachers, three parents, and seven students. Data were collected through interviews with a total of thirteen respondents. The findings reveal three key points. First, teachers consistently instill the concepts of Hiri and Ottappa in the learning process as a preventive measure against bullying. Second, these values are implemented through advice, habituation, and character strengthening in classroom activities. Third, their application has proven effective in transforming students’ behavior positively and reducing bullying incidents within SMB. Therefore, Hiri and Ottappa serve as ethical-religious approaches that are relevant for character formation and for preventing bullying, both in Buddhist Sunday Schools and in formal educational settings.